A small state addressing big problems: Perspectives on recent Danish foreign and security strategy - Jessica Larsen (Danish Institute for International Studies (DIIS), 2020)
With the change of government in 2019 to a Social Democratic leadership, the future of Danish foreign and security strategy is uncertain - not only its substance but also whether dedicated strategizing will be continued. This question is only becoming more urgent with the global reach of the corona crisis. The report finds that for a small state operating in a volatile geopolitical environment and addressing complex crises, a dedicated foreign and security strategy can play an important role. Four fundamental benefits are discussed: To the extent that a foreign and security strategy communicates position and priorities, it can sharpen Denmark's international identity and be a one stop shop to partner states and adversaries alike. As a government-sanctioned document, it can allow a small state to be pro-active and agenda-setting internationally, rather than following its larger allies. A strategy can support domestic political debate on foreign and security policy, because the actual drafting process is fundamentally inter-minsterial. The publication of a strategy can provide a much-needed occasion to cultivate democratic and political scrutiny through regular public debate.
Keywords: 300; Außenpolitik; Internationale Sicherheit; Dänemark